Development of dietary soluble fibres by enzymatic synthesis and assessment of their digestibility in in vitro, animal and randomised clinical trial models. (3rd October 2017) - Hasselwander, Oliver; DiCosimo, Robert; You, Zheng; Cheng, Qiong; Rothman, Steven C.; Suwannakham, Supaporn; Baer, Zachary C.; Roesch, Brian M.; Ruebling-Jass, Kristin D.; Lai, Jian Ping; Hurteau, Richard E.; Marquez, Mario L.; et al.
Abstract: The aim was to develop novel fibres by enzymatic synthesis, to determine their total dietary fibre by AOAC method 2009.01 and to estimate their potential digestibility and assess their digestibility in vivo using glycaemic and insulinaemic responses as markers in mice and randomised clinical trial models. We found that fibre candidates to which α-(1, 2) branching was added were resistant to digestion in the mouse model, depending on the amount of branching. These results show that in vivo models are needed to reliably assess the digestibility of α-glycosidic-linked oligomeric dietary fibre candidates, possibly due to absence of brush border α-glucosidase activity in the current in vitro assessment. α-(1, 3)-linked and α-(1, 6)-linked glucose oligomers were completely digested in humans and mice. In conclusion, it is possible to develop dietary soluble fibres by enzymatic synthesis. Adding α-(1, 2) branching increases their resistance to digestion in vivo and can thus improve their suitability as potential fibre candidates. Clinical Trial Registry: ClinicalTrials.gov, NCT02701270